2003
DOI: 10.1126/science.1084909
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Cells by Flipped SNAREs

Abstract: The SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) hypothesis suggests that pairs of proteins known as vesicle (v-) SNAREs and target membrane (t-) SNAREs interact specifically to control and mediate intracellular membrane fusion events. Here, cells expressing the interacting domains of v- and t-SNAREs on the cell surface were found to fuse spontaneously, demonstrating that SNAREs are sufficient to fuse biological membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
204
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 224 publications
(219 citation statements)
references
References 28 publications
10
204
0
5
Order By: Relevance
“…Using a cell fusion assay, previous studies showed that cells expressing v-and t-SNAREs on the cell surface fuse spontaneously, demonstrating that SNAREs are sufficient to fuse biological membranes [10]. VAMP3 binds to plasma membrane t-SNAREs syntaxin1, syntaxin4, SNAP-23 and SNAP-25 [22,29,30,34].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a cell fusion assay, previous studies showed that cells expressing v-and t-SNAREs on the cell surface fuse spontaneously, demonstrating that SNAREs are sufficient to fuse biological membranes [10]. VAMP3 binds to plasma membrane t-SNAREs syntaxin1, syntaxin4, SNAP-23 and SNAP-25 [22,29,30,34].…”
Section: Resultsmentioning
confidence: 99%
“…Using a cell fusion assay [10], we report here that VAMP3 forms fusogenic pairing with t-SNARE complexes syntaxin1/SNAP-25, syntaxin1/SNAP-23 and syntaxin4/SNAP-25, but not with syntaxin4/SNAP-23.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations